Modeling Radioimmune Response—Current Status and Perspectives - Friedrich, Thomas; Henthorn, Nicholas; Durante, Marco (Frontiers in Oncology, 2021)
The combination of immune therapy with radiation offers an exciting and promising treatment modality in cancer therapy. It has been hypothesized that radiation induces damage signals within the tumor, making it more detectable for the immune system. In combination with inhibiting immune checkpoints an effective anti-tumor immune response may be established. This inversion from tumor immune evasion raises numerous questions to be solved to support an effective clinical implementation: These include the optimum immune drug and radiation dose time courses, the amount of damage and associated doses required to stimulate an immune response, and the impact of lymphocyte status and dynamics. Biophysical modelling can offer unique insights, providing quantitative information addressing these factors and highlighting mechanisms of action. In this work we review the existing modelling approaches of combined ‘radioimmune’ response, as well as associated fields of study. We propose modelling attempts that appear relevant for an effective and predictive model. We emphasize the importance of the time course of drug and dose delivery in view to the time course of the triggered biological processes. Special attention is also paid to the dose distribution to circulating blood lymphocytes and the effect this has on immune competence.